Nilai-nilai Pendidikan Akhlak dalam Sepuluh Perintah Allah (Telaah Tafsir Surah Al-An’am dan Al-Isra’) - meidatus sadiyah; habibi al amin (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2022)
The value of moral education contained in Surah Al-An'am verses 151-153 and Al-Isra' 23-39 The Koran is the word of Allah SWT has instilled character values ​​in Q. S. al-An'am verses 151-153 and Al-Isra 23-39 in the form of an education, namely the value of faith, the value of piety, devotion to parents, the value of responsibility, the value of love for peace, the value of justice, giving rights to relatives, prohibition of extravagant behavior, prohibition of being stingy, and prohibition of arrogance. 2) Application of the value of moral education in Al-An'am verses 151-153 and Al-Isra' 23-39 in life there needs to be a habituation interaction relationship carried out by the family by behaving by giving assistance to relatives, giving sodaqoh, gifts, not to waste wealth in a wasteful manner and then supported by the school in inculcating 18 personality or character values ​​in the form of tolerance, discipline, hard work, religious, love for the homeland, appreciating achievement, communicative, honest, creative, independent, democratic, fond of reading, caring environment, social care, curiosity, national spirit, love of peace, and responsibility.